Business in blue jeans : how to have a successful business on your own terms, in your own style - Baroncini-Moe, Susan, (Sound Wisdom, 2013)
"In Business in Blue Jeans: How to Have a Successful Business on Your Own Terms, in Your Own Style, you'll learn how to create and grow a business that works for you. More than just a "how-to" guide, Business in Blue Jeans contains actionable, practical strategies..." -- jacket flap.